The Analysis Of Performance Quality And Human Resource Communication In The Regional Finance And Asset Management Office Of Semarang City - Anita Muin Aprilianingrum; Haryani Haryani; Karjono Karjono; Budi Purnomo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The implementation of regional autonomy as an embodiment of the concept of decentralization is intended so that regional governments can further increase their efficiency and effectiveness in administering government, carrying out development, and providing services to the community more optimally by the characteristics of their region. A communication gap between superiors and subordinates occurs, triggering the emergence of negative Human Resource (HR) perceptions regarding the communication mechanisms between superiors and subordinates in the organization. This research used an explanatory research method, namely explaining the relationship between performance quality variables and communication quality. The sample selection used was stratified random sampling. The sample used was 100 Regional Financial and Asset Management Service (RFAMS) officers. The data analysis method in this research used SPSS (Statistical Package for Social Science). The research results show that performance and communication quality greatly influence commitment. Therefore, management should be able to design a sophisticated information system so that the performance and the communication of existing HR can be appropriately monitored.